(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The study provides a scholarly analysis based on concrete factual material, demonstrating that a literary character is portrayed in dialectical interaction with other characters of the work, thereby constituting the overall system of images. It is shown that the system of images in a literary text simultaneously reflects the objective relations existing within the depicted social reality, the author’s stance toward these relations, as well as the author’s attitude toward the described reality and existence.